Building platelet phenotypes: Diaphanous-related formin 1 (DIAPH1)-related disorder. (3rd April 2022) - Rabbolini, David; Liang, Hai Po Helena; Morel-Kopp, Marie-Christine; Connor, David; Whittaker, Shane; Dunkley, Scott; Donikian, Dea; Kondo, Mayuko; Chen, Walter; Stevenson, William S; Campbell, Heather; Joseph, Joanne; et al.
Abstract: Variants of the Diaphanous-Related Formin 1 ( DIAPH-1 ) gene have recently been reported causing inherited macrothrombocytopenia. The essential/"diagnostic" characteristics associated with the disorder are emerging; however, robust and complete criteria are not established. Here, we report the first cases of DIAPH1 -related disorder in Australia caused by the autosomal dominant gain-of-function DIAPH1 R1213X variant formed by truncation of the protein within the diaphanous auto-regulatory domain (DAD) with loss of regulatory motifs responsible for autoinhibitory interactions within the DIAPH1 protein. We affirm phenotypic changes induced by the DIAPH1 R1213X variant to include macrothrombocytopenia, early-onset progressive sensorineural hearing loss, and mild asymptomatic neutropenia. High-resolution microscopy confirms perturbations of cytoskeletal dynamics caused by the DIAPH1 variant and we extend the repertoire of changes generated by this variant to include alteration of procoagulant platelet formation and possible dental anomalies.